from the given equation sum of roots a + b = 1
Product of roots ab = 1
Now a2 + b2 = (a + b)2-2 a b
= 1 – 2
= - 1.
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
RELATED QUESTIONS :
–x2 +RD Sharma - Mathematics
Solve the fRD Sharma - Mathematics